2018
DOI: 10.29252/nirp.jpcp.6.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Style and Emotion Regulation in Mothers of Preschool Children

Abstract: Objective: The aim of the study was to compare emotion regulation among the authoritative, authoritarian and permissive parenting styles of mothers with preschool children. Methods:The statistic community of this study was all the mothers in Tehran who had preschool children aged between 4 and 6 years. By convenient sampling, 8 kindergartens were selected, and the questionnaires were completed by mothers. The sample consisted of 270 mothers with preschool children. The participants completed the questionnaires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
1
6
0
1
Order By: Relevance
“…Fonseca et al (2020) found relations between parental stress and styles were partly mediated by parental ER. The role of parental ER in these relations is further supported by findings that authoritarian and permissive parents exhibit poorer ER than authoritative parents of children aged 4-6 years (Bahrami et al, 2018). Thus, in the face of caregiving stress, parents with poor ER might be more likely to rely on insensitive parenting techniques, perhaps as means of quickly extinguishing the source of their distress like child misbehaviour (Fabes et al, 2001).…”
Section: Parental Stress Predicting Parenting Stylesmentioning
confidence: 89%
See 1 more Smart Citation
“…Fonseca et al (2020) found relations between parental stress and styles were partly mediated by parental ER. The role of parental ER in these relations is further supported by findings that authoritarian and permissive parents exhibit poorer ER than authoritative parents of children aged 4-6 years (Bahrami et al, 2018). Thus, in the face of caregiving stress, parents with poor ER might be more likely to rely on insensitive parenting techniques, perhaps as means of quickly extinguishing the source of their distress like child misbehaviour (Fabes et al, 2001).…”
Section: Parental Stress Predicting Parenting Stylesmentioning
confidence: 89%
“…Those with poorer ER tended to rely on more authoritarian techniques, perhaps as means of quickly extinguishing child misbehaviour for sake of their own distress (Fabes et al, 2001). Indeed, Bahrami et al (2018) found authoritarian parents exhibited the poorest ER of the parenting style groups. Parental positive adjustment was negatively related to permissive but not related to authoritarian parenting.…”
Section: Discussionmentioning
confidence: 99%
“…10 Parents who use authoritative parenting have higher emotional regulation than parents who use permissive parenting. 13 The results of other studies have shown that parenting styles for tau people can affect children's mental health and self-esteem. 14 The results of other studies show that authoritative parenting is able to enhance one's personal growth initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…Children with ASD who are raised in authoritarian parenting are unable to control themselves. Bahrami, Dolatshahi, Pourshahbaz, & Mohammadkhani 13 describes the relationship between parenting patterns and tempertantrums of children with ASD, and it is found that the more parents do authoritarian parenting, the more the tempertantrum intensity in children, conversely, the lower the authoritarian parenting applied, the lower the tempertantrum intensity in the autistic child. Thus authoritarian parenting will have a negative impact on children's development because children have difficulty developing their potential.…”
Section: Discussionmentioning
confidence: 99%